OPERATIONAL PERFORMANCE AND SERVICE LEVEL OF MALANG CITY PUBLIC TRANSPORT LDH/G DURING THE COVID-19 PANDEMIC - Prijono Bagus Susanto, Lizzatul Munajat (Universitas Negeri Malang, 2021)
Abstract: Competition for transportation modes such as ojol causes a lack of interest in passengers using angkot. Some of the other impacts caused by Covid-19 on city transportation, namely, a decrease in the number of passengers from 15 people in normal conditions to only around 3-4 people in the Covid-19 pandemic in one trip During the Covid-19 pandemic many angkot stopped operating because it was very hard to get passengers. So not infrequently some angkot finally turn back to the departure terminal and end up returning home from work at noon. The method used is by distributing questionnaires to drivers and users of angkot suits for characteristics and for the level of service, where for the level of service followed by data processing using the IPA method with a Likert scale. For operational performance, static and dynamic field surveys are carried out. Based on the results of the research, the results of the operational performance of LDH/G public transportation are between 2-11 minutes in the good category, the travel time is 51 minutes in the good category, and the circulation time is 1 hour 28 minutes in the good category. As for the level of service that needs to be improved, namely the convenience aspect in the form of the availability of trash bins, the health protocol aspect of having a cross (X) on the seat and the availability of trash bins. For the level of service that needs to be maintained, namely the security aspect in the form of vehicle identity and the presence of lights, the safety aspect in the form of vehicle feasibility, the comfort aspect of passenger capacity and the presence of windows, the affordability aspect in the form of route suitability, the suitability of the tariff paid, and the health protocol aspect in the form of service user obligations. wearing a maskKeywords: public transportation, operational performance and service level